Pentingnya kesehatan mental dalam menjaga harmoni keluarga - Maelana, Herman Wahyu Dwi; Wijayanti, Irine Diana Sari; Siyamto, Yudi; Ngatipan; Fathoni, Muhammad Isnaini (Nur Science Institute, 2025)
The mental health of each family member has a significant impact on family well-being. This community service aims to raise public awareness about the importance of mental health in supporting family well-being through a counseling session held at Pendopo Padukuhan Gonjen RT 08, Tamantirto, Kasihan, Bantul. The methods used include lectures and interactive discussions, attended by 30 participants, comprising heads of families and their family members. The results of the counseling session indicated that many participants were previously unaware of the impact of mental health issues such as stress and anxiety on family relationships. Through the lecture, participants gained knowledge about the signs of mental health problems and learned ways to manage stress and enhance emotional well-being. The discussion allowed participants to engage actively, share their experiences, and gain a deeper understanding of the role of mental health in maintaining a harmonious family life. This community service activity highlights the importance of enhancing mental health literacy to promote family well-being and address the psychological challenges that impact family dynamics.